Perkawinan dalam Narasi Leluhur: Studi Menghargai Kekudusan Perkawinan dalam Protestan pada Pemuda Pemudi HKBP Palembang menurut Kejadian 16:1-5 - Sukanto Limbong (Bulletin of Community Engagement, 2024)
Marriage is a union between a man and a woman aimed at bringing the couple together and producing offspring. In the context of Middle Eastern culture, a family is considered complete when it has a male child as an heir, leading to a perception that women who cannot bear children are often devalued and neglected. This study employs critical historical interpretation methods to understand biblical texts, particularly Genesis 16:1-5, which illustrates the dynamics between Sarai, Abram, and Hagar. The research was conducted at HKBP Palembang on October 8, 2022, focusing on church youth facing social pressures and identity searches. Data were collected through in-depth interviews, literature studies, and participatory observations. The findings reveal that many youths feel pressured by social expectations and seek recognition within their faith context. This study aims to develop more effective mentoring programs for youth, considering ethical aspects and the confidentiality of informants. Through this approach, it is hoped that ways can be found to demonstrate God's presence in the lives of contemporary youth